Techlance - Mobeen Nazar (Journal of Computing Technologies and Creative Content, 2025)
Our Research and Project ‘TECHLANCE’ is on a Web Application related to the Freelancing Platform. Techlance is a website that provides many features to their users like users create their profiles, creating services, post a request for services and send offers services other users can deal with these services. Users have a dashboard in which all the menus include edit a profile, settings, reviews, favorites, projects, Account balance, and Get credits. Admin Panel is used by the admin which includes user profile management, services management, request management, comment management, price type management, etc. Techlance is focused on the field of Information Technology (IT) to promote the field of IT.The HangFire module is used for scheduling all the tasks in the background. The Hand Fire tool is used in the HangFire module. Our services are limited to the technical domain only which includes, Web Development, Word Press Development, technical writing, Programming, and many more technical services.